"La Cantuta" Publishing Fund of the Enrique Guzmán y Valle National University of Education (OAindex, 2022)
The Editorial Fund "La Cantuta" of the Enrique Guzmán y Valle National University of Education is a publishing house that has the vocation of disseminating and spreading scientific knowledge, generated by the entire scientific community in general, in the national and international context through the publication of open access digital books.This publishing house makes scientific works of rigor available to society while offering the entire scientific community a channel to publish their works, maintaining disciplinary quality standards, such as blind refereeing, similarity review, copyright protection, ISBN (International Standard Book Number) registration, DOI (Digital Object Identifier) ​​registration, publication with metadata, query metrics and participation in indexing. We have the publishing house registration with the National Library of Peru, our PUBLISHING HOUSE operates based on the OMP (Open Monograph Press) system and the editorial board is made up of prominent researchers attached to prestigious universities at national and international level.